Modelling and simulation of power electronic systems using a bond graph formalism - Rui Manuel Esteves Araújo (2002)
This paper deals with the modelling of powerelectronic systems using the bond graph formalism.The switching components are modelled using anideal representation so that a constant topologysystem is obtained. The purpose of the presentcontribution is to discuss a technique that combinesbond graph energy-flow modelling and signal-flowmodelling schemes for simulation and prototypingof signal processing algorithms in powerelectronics systems. In this paper, we will discussmodels of the use of fully-controlled, semicontrolledand non-controlled switches in the fieldof power static converters. By concept, asimulation environment can be examined atdifferent abstraction or hierarchy levels. Theapproach in this paper is, accordingly, theformulation of a simulation task at different levels:component level, topology level, functionaldescription and implementation description. Thepaper concludes with two practical examples ofsimulation of power electronics systems.